Impacts of chronic intermittent ethanol vapor and predator odor on ethanol intake and striatal D1 and CB1 cannabinoid receptor-expressing medium spiny neurons - Cristiane Aparecida Favoretto; Cristiane Aparecida Favoretto; Allyson Nguyen; Gabriela R. Chacon; Amanda J. Roberts; Tali Nadav; Saumya Ranjan; Luisa Becker Bertotto; Fábio Cardoso Cruz; Eric P. Zorrilla (Frontiers in Neuroscience)
IntroductionStress is a risk factor for ethanol use disorders, which has been modeled by chronic intermittent ethanol (CIE) vapor exposure. Repeated stress alters CB1 receptor signaling, which could influence ethanol-related behaviors. Striatal CB1 receptors regulate D1-medium spiny neurons (D1-MSNs), involved in goal-directed behaviors and stress responses. This study tested the hypothesis that predator odor stress interacts with CIE exposure to: (1) increase or accelerate CIE-induced escalation in ethanol intake, (2) increase plasma corticosterone levels, and (3) increase the expression or co-localization of CB1 receptors, D1-MSNs, and Fos neuronal activation marker in the nucleus accumbens (NAc), dorsomedial (DMS), and dorsolateral (DLS) striatum.MethodsMale C57BL/6J mice underwent three cycles of 4 days CIE or air exposure, alternated with 5 days ethanol access. During the last two cycles, mice were exposed to predator odor or control bedding before each drinking session. Following the last stressor, brains were processed for RNAscope to label Cnr1 (encodes CB1), Drd1 (D1), and Fos (Fos).ResultsAs hypothesized, predator odor accelerated the CIE-induced increase in ethanol intake. Contrary to our expectations, CIE did not alter corticosterone levels after the final stressor. Compared to control bedding, predator odor reduced the percentage of Fos+ and triple-labeled Cnr1/Drd1/Fos+ cells in NAc, but not dorsal striatum. In addition, CIE vs. Air exposure, increased percentages of Fos+, double-labeled Cnr1/Fos+, Drd1/Fos+, and triple Cnr1/Drd1/Fos+ cells in the NAc, but not DMS or DLS.DiscussionThus, CIE and stress elicited opposite neuroactivational effects on CB1-regulated D1-MSNs of the NAc. The role of these changes in stress- and CIE-augmented drinking warrants further investigation.